「促進學習的評估」改革： 學校的實施與挑戰 The Reform of "Assessment for Learning": School Implementation and Challenges - 陳健生Jacqueline Kin-Sang Chan; 甘國臻Kerry John Kennedy; 霍秉坤Ping-Kwan Fok (Higher Education Foundation, 2010)
自2001年香港實施大規模的課程改革以來，學校評估也相應地改革以配合課改的需要，「促進學習的評估」是其中的改革重點，它對傳統上以考試為主導的評估來說，是重要的改革和挑戰。在意念上，「促進學習的評估」重視評估和學習的關係，側重提升評估的質素，對學校和教師在改善課堂評估方面尤為重要。本文的目的是透過香港六所學校的實施個案，探討有關的評估改革實施，以及學校所面對的挑戰。研究結果顯示，學校在總體發展計畫、具體措施、課堂教學及評估方面，對中央文件所提的「促進學習的評估」都有不同程度的理解和實施。總體上，學校對評估的革新取向，採取由上而下的實施措施，反映學校對評估改革的概念和取向，並未有深入的認識和發展策略，而學校教師在課堂實施方面，仍然以總結性評估為主要的考慮，對知識為主的課堂傳授及測考較為重視，顯示「促進學習的評估」其實施過程遇到不少的困難和挑戰，包括學校實施者對有關理念的重視和理解、學校發展的環境脈絡和困難，以及社會的價值和文化取向等，都不能掉以輕心。 Since 2001, Hong Kong has initiated and adopted a large-scale curriculum reform, of which "assessment for learning" (AfL) is used to best suit the spirit of the reform. AfL , as a significant reform in assessment, has posed a challenge for the traditional examination-oriented assessment in Hong Kong. In essence, AfL promotes the relationship between assessment and learning. It also functions as a way to improve the quality of assessment and thus becomes a significant aspect of improving classroom assessment for schools and teachers. This study aims to explore the implementation of AfL and the challenges met through six case studies. The results found that there were different interpretations and implementation of AfL in school planning, implementation measures, classroom teaching and assessment practice. It showed that the implementation was a top-down strategy and school did not have an in-depth understanding of the concept of AfL and development strategies. Classroom implementation reflected that teachers' major concerns were summative assessments. Knowledge delivery and test and examinations still prevailed. It showed that there were difficulties and challenges in the implementation of AfL which included the different interpretations of AfL by the school implementers, the difficulties of implementation in individual school contexts and the dominated social values and cultures.